Economic policy and confidence of economic agents: A causal relationship? - Silvo Dajčman (Review of Economic Perspectives, 2020)
The purpose of this paper is to study whether innovations in monetary and fiscal policy are a leading indicator of future business and consumer confidence and reverse applying the panel Granger causality analysis to two periods in the history of the euro area: before and after the start of the Great Recession. The results show that Granger causality interaction between the confidence of economic agents and the stance of monetary policy (measured by the shadow rate) is stronger than between the former and the fiscal policy instruments. The European Central Bank (ECB) shadow rate innovations Granger caused business and consumer confidence in both periods, but also indicators of confidence Granger caused the shadow rate. No such feedback could be established between two fiscal policy instruments (government expenditure and revenue growth) and the indicators of confidence. Government spending and revenues Granger caused business confidence in the first subperiod, but not in the second subperiod when the causality reversed. The government revenues Granger caused consumer confidence in the first subperiod, while government expenditures in the second subperiod. Consumer confidence Granger caused government spending in the first subperiod.
Keywords: E52; E62; E63; H31; H32; 330; fiscal policy; monetary policy; consumer confidence; business confidence; panel Granger causality